A study to determine the attitudes of medical and non-medical students towards disability - DR. GRACE LYDIA SAROJINI; R.VIDHYA LAKSHMI (International Journal of Pharma and Bio Sciences, 2017)
The purpose of this study was to determine the attitudes of Medical and Non –Medical students towards disability. 250 Medical and 250 Non–Medical Students were included based on the inclusion and exclusion criteria. Non-probability, random sampling was used. All participants were administered individually with Attitude towards disabled persons (Form - O) scale questionnaire to measure the level of Attitudes. Results of the study explains that both Medical and Non – Medical students have a negative attitude towards disabled persons and hence there is no statistical significance difference between both the groups but however those students who had contact with persons with disabilities have a more positive attitude by SPSS (V 15.0) with the alpha level set at 0.05. Attitudinal scores were found to be negative for both Medical and Non-Medical students. The study reveals that there is no statistical significant difference in attitudes among both the groups.